Volume 7: Turbomachinery, Parts A, B, and C 2010
DOI: 10.1115/gt2010-22107
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Merits of CFD for the Performance Prediction of a Low Pressure Steam Turbine Radial Diffuser

Abstract: The performance of the last stage and the diffuser of a low pressure steam turbine module are inherently linked. Design alterations in one part must take into consideration the subsequent effects imposed upon the other. Through a linked design system, including both the last stage and the exhaust, the last stage performance can be predicted more accurately and hence further performance improvements are possible. The importance of a valid prediction for the effects of the diffuser upon last stage power and effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…This has proven to be the one of the most robust with the methodology, integrated with state of the art CFD codes; still used by a leading industrial supplier over 15 years later [1,14]. The hood inlet is circumferentially divided into segments, shown in Fig.…”
Section: Numerical and Experimental Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This has proven to be the one of the most robust with the methodology, integrated with state of the art CFD codes; still used by a leading industrial supplier over 15 years later [1,14]. The hood inlet is circumferentially divided into segments, shown in Fig.…”
Section: Numerical and Experimental Methodologiesmentioning
confidence: 99%
“…Tindell's numerical analysis with representative inlet conditions showed the separation point was dependent upon the operating point of the turbine. Accurate prediction of the separation point is vital, as Beevers observed in 2010 [1], the earlier the separation the less pressure the diffuser can recover. Liu in 2003 [13] investigated the effect of inlet conditions, comparing uniform with distorted inflow, and found separation was only present with nonuniform distributions at inlet to the diffuser.…”
Section: Separation Along the Bearing Conementioning
confidence: 98%
See 1 more Smart Citation
“…Details of the operation point are not published. The data for Beevers [20] is taken from an 10% scale test facility at Alstom Power operating at comparable Mach number to field data. As the published data does not include an x-axis scale, a zero point is assumed for comparision.…”
Section: Stage Resultsmentioning
confidence: 99%
“…Second order discretization was applied and the turbulence was modelled with the standard k-ε turbulence model with standard wall functions. This turbulence model was selected as it is widely adopted by other researchers [22,20,12]. Ris et al (2009) showed a small difference in the calculated pressure recovery (approximately 5%) with varying turbulence models [23].…”
Section: Calculation Set-upmentioning
confidence: 99%